2017
DOI: 10.1021/acscatal.7b00053
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Nitrogen Functionalization of Porous Carbon: Toward Immobilizing Highly Active Palladium Nanoclusters for Dehydrogenation of Formic Acid

Abstract: Highly dispersed palladium nanoclusters (Pd NCs) immobilized by a nitrogen (N)-functionalized porous carbon support (N-MSC-30) are synthesized by a wet chemical reduction method, wherein the N-MSC-30 prepared by a tandem low-temperature heat-treatment approach proved to be a distinct support for stabilizing the Pd NCs. The prepared Pd/N-MSC-30 shows extremely high catalytic activity and recyclability for the dehydrogenation of formic acid (FA), affording the highest turnover frequency (TOF = 8414 h–1) at 333 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(121 citation statements)
references
References 44 publications
4
116
1
Order By: Relevance
“…[75,76] However, MNPs are unstable on "naked" carbon because of the weak interactions between metal species and carbon surfaces, leading to low catalytic activities. [79] It was observed that the N-groups of the porous carbon could control the size and dispersion of the Pd nanoclusters. [77] An impressive TOF up to 2623 h −1 at 50 °C for FADH was achieved.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[75,76] However, MNPs are unstable on "naked" carbon because of the weak interactions between metal species and carbon surfaces, leading to low catalytic activities. [79] It was observed that the N-groups of the porous carbon could control the size and dispersion of the Pd nanoclusters. [77] An impressive TOF up to 2623 h −1 at 50 °C for FADH was achieved.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Reproduced with permission [79]. Inset shows corresponding TOF values of the dehydrogenation of FA over the catalysts.…”
mentioning
confidence: 99%
“…[1] However, the efficient production, release and controllable storage of hydrogen still remain challenging issues. Hydrogen (H 2 ) has been generally regarded as one of the propitious energy carriers to meet the growing demand for a clean and sustainable energy supply.…”
Section: Introductionmentioning
confidence: 99%
“…When the growth rate is greater than the nucleation rate of PMNCs, this leads to the overgrowth of PMNCs, that is, nanocrystals with the larger sizes . To enhance the affinity between carbon supports and metal precursors/nanocrystals, doping carbon supports with heteroatoms (e.g., S and N) has been reported by Nazar, Xu, and our group . Heteroatom dopants show strong affinity to metal precursors/nanocrystals, which essentially anchor nanocrystals through metal−N and metal−S bindings.…”
Section: Figurementioning
confidence: 92%